PENGEMBANGAN PERMAINAN DADU HURUF PADA KEMAMPUAN KOGNITIF ANAK USIA DINI 5-6 TAHUN - Novita Sari, Ana (Fakultas Keguruan dan Ilmu Pendidikan Univesitas Dharmas Indonesia, 2023)
This research was carried out to overcome the lack of learning media that did not attract the attention of children at Aisyiyah 01 Koto Baru Kindergarten, which had an impact on their disinterest in participating in learning. Efforts were made to utilize letter dice games as a means of supporting learning that is able to attract children's interest and help them in the learning process. Research and development is carried out by following the ADDIE model which consists of the Analysis, Design, Development, Implementation, and Evaluation stages. The results of the validation assessment of the letter dice game in improving cognitive development by three experts showed an average score of 79%, which indicates that this game is included in the valid category. The practicality test shows an average score of 97.32%, indicating that the letter dice game is very practical to use. While the results of the effectiveness of the letter dice game show an average score of 85%, with 14 children at the BSB stage (Good Very Good) and 1 child still at the MB stage (Not yet). With this percentage, the effectiveness of the game is categorized as very effective. Based on the above analysis, it can be concluded that letter dice game is effective in enhancing cognitive development and facilitating children's understanding in the learning process. This research resulted in a letter dice game that is very valid, very practical, and very effective.